Typing of clinical and reference strains of Saccharomyces cerevisiae using pulsed-field gel electrophoresis and MALDI-TOF MS - Justyna Cieślik; Zofia Bakuła; Katarzyna Roeske; Aleksandra Kuryłek; Alicja Okrasińska; Jacek Bielecki; Marta Wróblewska; Tomasz Jagielski (Scientific Reports)
Abstract In recent years matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has emerged as a rapid and reliable tool for microbial identification and diagnosis. However, its use for molecular typing of S. cerevisiae has been investigated in a limited number of studies, mainly based on brewing strains. The purpose of the study was to compare the results of the gold standard pulsed-field gel electrophoresis (PFGE) typing with MALDI-TOF MS on a subset of S. cerevisiae clinical and reference strains. The study comprised 50 clinical isolates, collected from single patients hospitalized in the Central Clinical Hospital of the Medical University of in Warsaw between 2014 and 2016. Furthermore eight reference strains i.e. three probiotic, four baker and one winery strains, were included. Strain typing was performed using PFGE and MALDI-TOF MS. PFGE split the study sample into six clusters and two unique profiles. Whereas MALDI-TOF MS typing produced five clusters. Overall, the results of PFGE and MALDI-TOF MS were congruent for all (49/50; 97%) but one clinical isolates. In both analyses, three probiotic strains, unlike baker’s and winery strains, clustered only with clinical isolates. Although PFGE had a higher resolution capacity than MALDI-TOF MS, both methods allowed for a clear discrimination between clinically relevant (clinical & probiotic) and irrelevant (baker’s and winery) strains. This is the first time that MALDI-TOF MS has proven useful in the epidemiological studies of S. cerevisiae.